2018
DOI: 10.2147/ijn.s181052
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <em>Mycobacterium tuberculosis</em> purified ESAT-6 (Rv3875) by magnetic bead-coupled gold nanoparticle-based immuno-PCR assay

Abstract: PurposeImmuno-PCR (I-PCR), an ultrasensitive method, combines the versatility of ELISA with the exponential amplification capacity of PCR. Coupling of detection antibodies with the reporter DNA is a critical step of I-PCR. Gold nanoparticles (GNPs) and magnetic beads (MBs) are relatively easy to attach with the antibodies and DNA. Therefore, we designed MB-coupled GNP-based I-PCR (MB-GNP-I-PCR) assay for the detection of Mycobacterium tuberculosis antigen.MethodsGNPs were synthesized by chemical reduction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Similar to the iqPCR method reported herein, previous immuno-PCR methods also demonstrated better sensitivity than corresponding traditional immunoassays [ 23 , 24 , 32 34 ]. The use of beads, rather than plates for antibody-mediated capsid capture in iqPCR also created an opportunity to perform an elution step.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar to the iqPCR method reported herein, previous immuno-PCR methods also demonstrated better sensitivity than corresponding traditional immunoassays [ 23 , 24 , 32 34 ]. The use of beads, rather than plates for antibody-mediated capsid capture in iqPCR also created an opportunity to perform an elution step.…”
Section: Discussionsupporting
confidence: 56%
“…We, therefore, sought to develop a novel AAV capsid detection method that would have comparable sensitivity to conventional qPCR methods used for measuring total vector DNA in clinical shedding studies [ 1 , 2 ]. To this end, we utilized the format of immunocapture-based qPCR (iqPCR), described previously to detect intact adenovirus particles, microbial antigens, and cytokines [ 20 24 ]. The method described herein capitalizes on the high target specificity of monoclonal antibodies directed against the AAV5 capsid and the exceptional sensitivity offered by qPCR detection of encapsidated vector DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Immuno-PCR is a technique which combines amplification of DNA by PCR and coupling with ELISA technique. This was refined by the use of TB-specific Mycobacterium tuberculosis purified ESAT-6 (Rv3875) by magnetic bead-coupled gold nanoparticle-based immuno-PCR assay which has higher sensitivity compared with conventional immuno-PCR [23]. For the fast and efficient detection of TB, the use of mycolic acids of tuberculin bacilli was also described.…”
Section: Discussionmentioning
confidence: 99%
“…To detect mycobacterium tuberculosis MPT64 and CFP-10 proteins in the bodily fluids of TB patients, an MB-AuNP-I-PCR assay was designed using the functionalized gold nanoparticles (AuNPs) coupled with detection antibodies, oligonucleotides and magnetic beads (MBs), and found that sensitivity was much higher than magneto-ELISA and GeneXpert assays. This, thus, suggeststhat it leads to the development of a diagnostic kit [ 207 ]. In a study, a gold nanoparticle probe-based assay (GNPA) was developed for the detection of hepatitis C virus’ (HCV) core antigen.…”
Section: Nanomaterials and Their Clinical Applicationmentioning
confidence: 99%